As populações urbanas de Centris (Heterocentris) analis Fabricius, 1804 (Hymenoptera, Apidae, Centridini) são geneticamente estruturadas? - Rezende, Leandro Pereira (2019)
Most bees are solitary and some inhabit urban environments, finding refuge for their survival, supply their foraging and nesting needs. Centris (Heterocentris) analis is a multivoltine species with broad distribution, average size and polyletic behavior that nests in preexisting cavities. Females exhibit phylopatric behavior and males are considered the dispersing sex. Based on these characteristics, the central objective of this work was to test the hypothesis that urban populations of C. analis are not genetically structured. Further aims were to perform niche modeling and reevaluate the intranidal sociogenetic structure. We analyzed 221 individuals from 21 localities collected between 2012 and 2018. Based on the present collection records and those obtained from online surveys, ecological niche modeling was performed to determine potential areas of species distribution using the Maxent software implemented in ArcGis. Niche modeling showed that potential distribution areas occur from Mexico in North America to part of the state of Paraná in southern Brazil, including countries in South America. Sixteen species-specific microsatellite loci, with genotyping error rate of the loci from 0.00 to 2.17%, absence of linkage disequilibrium and null alleles were used to assess the genetic structuring of the populations analyzed. The FST pairwise values showed that the Teodoro Sampaio/SP and Cruzeiro do Sul/AC populations differed most from the other populations. The genetic diversity indexes showed high number of alleles (5.65) and allelic richness (4.58). AMOVA with two hierarchical levels showed FST value = 0.055 (p<0.0001) among populations. The analyses demonstrated low population structure, with no evident formation of geographically distributed genetic groups. The results of the Structure software (admixture model) show that the most probable scenario is the existence of a single genetic group for females and that males can be partially and equally assigned to three genetic groups in each locality. The TESS results did not delimit genetic groups. DAPC showed no structure for females and two not completely exclusive genetic groups in males. Intranidal genetic structure was assessed through 10 microsatellite loci in 30 individuals from eight nests. This analysis enabled confirming the monogyny-monandry mating system, in which a female mates with a single male during the nesting period. The results partially confirmed the proposed hypothesis, since low, but significant population structure was estimated, which was an expected result due to peculiar traits of the biology of the species. This work contributes knowledge on the biology and genetics of a solitary bee species that is very common in urban environments. There is a need for further studies of this nature on other species of solitary bees that occupy our cities (with broad or restricted distribution) for the purposes of comparison, since knowledge constitutes the first step toward the conservation of these species.